Iḥsās Ṭullāb Jāmi‘at ‘Alī bin Abī Ṭālib al-Islāmiyyah Ṭijāh Ṭaṭbīq Ṭanhaj an-Naḥw - Santoso, Nur Cholis Agus; Prayoga, Wildan Maulana (CV. Creative Tugu Pena, 2025)
This study discusses the perceptions of students at STAI Ali bin Abi Thalib Surabaya regarding the implementation of the Nahwu curriculum at STAI Ali bin Abi Thalib Surabaya. The curriculum functions to organize the learning process in a more directed and structured manner to achieve its objectives. Nahwu is one of the core courses at STAI Ali bin Abi Thalib Surabaya, and its implementation requires evaluation from students as a basis for improvement. This study uses a quantitative approach, and the type of research applied is phenomenological research. The data collected consists of students’ perceptions related to the implementation of the Nahwu curriculum. The data were analyzed using phenomenological analysis techniques with the following stages: reading questionnaire responses, categorizing data, coding data, determining themes, and describing the themes. The results of the study show that students at STAI Ali bin Abi Thalib Surabaya have diverse backgrounds in learning Nahwu. The majority of students consider the implementation of the Nahwu curriculum to be fairly good, both in terms of relevance to their needs, support for improving language skills, ease of understanding the material, and the challenges experienced by students in applying i‘rab. For future improvements to the Nahwu curriculum, students propose improvements in teaching methods, greater attention from teachers to students without a background in Arabic, the use of AI in teaching, and replacement of teaching modules.